Z-boson production in p-Pb collisions at √sNN=8.16 TeV and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; et al. (Journal of high energy physics, 2020)
Measurement of Z-boson production in p-Pb collisions at sNN$$ \sqrt{s_{NN}} $$= 8.16 TeV and Pb-Pb collisions at sNN$$ \sqrt{s_{NN}} $$= 5.02 TeV is reported. It is performed in the dimuon decay channel, through the detection of muons with pseudorapidity −4 < ημ < −2.5 and transverse momentum pTμ$$ {p}_{T}^{μ } $$> 20 GeV/c in the laboratory frame. The invariant yield and nuclear modification factor are measured for opposite-sign dimuons with invariant mass 60 < mμμ < 120 GeV/c2 and rapidity 2.5 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< 4. They are presented as a function of rapidity and, for the Pb-Pb collisions, of centrality as well. The results are compared with theoretical calculations, both with and without nuclear modifications to the Parton Distribution Functions (PDFs). In p-Pb collisions the center-of-mass frame is boosted with respect to the laboratory frame, and the measurements cover the backward (−4.46 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< −2.96) and forward (2.03 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< 3.53) rapidity regions. For the p-Pb collisions, the results are consistent within experimental and theoretical uncertainties with calculations that include both free-nucleon and nuclear-modified PDFs. For the Pb-Pb collisions, a 3.4σ deviation is seen in the integrated yield between the data and calculations based on the free-nucleon PDFs, while good agreement is found once nuclear modifications are considered.